2019
DOI: 10.3389/fcimb.2019.00044
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin Alters Intestinal Microbiota and Prevents Progression of Ankylosing Spondylitis in Mice

Abstract: Recently, accumulating evidence has suggested that gut microbiota may be involved in the occurrence and development of ankylosing spondylitis (AS). It has been suggested that rifaximin have the ability to modulate the gut bacterial communities, prevent inflammatory response, and modulate gut barrier function. The goal of this work is to evaluate the protective effects of rifaximin in fighting AS and to elucidate the potential underlying mechanism. Rifaximin were administered to the proteoglycan (PG)-induced AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 54 publications
(64 reference statements)
1
31
0
Order By: Relevance
“…In our previous clinical experiment, rifaximin caused only a slight change in intestinal flora [18]. However, the exact changes of the intestinal flora were not known [13,27]. Previous reports have shown that rifaximin inhibits the activation of NF-κB signaling pathway and downregulates the expression of inflammatory cytokines [27,28].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…In our previous clinical experiment, rifaximin caused only a slight change in intestinal flora [18]. However, the exact changes of the intestinal flora were not known [13,27]. Previous reports have shown that rifaximin inhibits the activation of NF-κB signaling pathway and downregulates the expression of inflammatory cytokines [27,28].…”
Section: Discussionmentioning
confidence: 84%
“…However, the exact changes of the intestinal flora were not known [13,27]. Previous reports have shown that rifaximin inhibits the activation of NF-κB signaling pathway and downregulates the expression of inflammatory cytokines [27,28]. Rifaximin could reduce the concentrations of TNF-α, IL-6, and endotoxin in patients with decompensated cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment with rifaximin can attenuated the imbalance of these microbiota [ 31 ]. Rifaximin can restore the unbalance of fecal microbiota in DSS-induced colitis mice [ 32 , 33 ]. In addition, rifaximin is a poorly absorbed semi-synthetic rifamycin antibiotic and gut-specific human PXR agonist [ 34 ].…”
Section: Discussionmentioning
confidence: 99%